Descriptions of eight new species of Phaelota (Coleoptera: Chrysomelidae) with a new generic synonymy and a key to species of Indian subcontinent - Prathapan, K. D.; Konstantinov, A. S. (Zootaxa, 2009)
Six new species of Phaelota Jacoby from India viz. P. assamensis, P. kottigehara, P. maculipennis, P. mauliki, P. saluki, and P. viridipennis and two new species from Sri Lanka viz. P. ogloblini and P. schereri are described and illustrated. Thrylaea Jacoby is treated as a new junior synonym of Phaelota. A lectotype for Phaelota variabilis (Jacoby) is designated and the species is removed from the synonyms of P. flavipennis (Motschulsky). The consequences of loss of flight on host plant selection in Phaelota are discussed and a key to the species of the Indian subcontinent is provided.